Anticardiolipin antibody in egyptian patients with chronic hepatitis c in correlation with liver injury - Mahmoud H Hemida; Shaaban S Alazhari; Ahmed El Borae Kabil; Abd El Halim Assem Elsherif; Mohamed Abd El Hameed Khedr (Wolters Kluwer Medknow Publications, 2017)
Background The presence of anticardiolipin (ACL) antibodies in chronic hepatitis C may be owing to induction of neoantigens by chronic viral infection, which may be because of disruption of liver cell membranes. The occurrence of these ACL antibodies may be observed because of recognition of these neoantigens by the immune system. Aim The aim of the work was to study the prevalence and clinical significance of ACL antibodies in chronic hepatitis C infection and their relationship with disease progression. Participants and methods Our study was performed on 90 individuals recruited from Gastroenterology and Hepatology Outpatient Clinics and Internal Medicine Department of Kafr Sheikh Institute. The participants were divided into the following three groups: group A consisted of 30 patients with chronic hepatitis C virus (HCV) infection with compensated liver cirrhosis, group B consisted of 30 patients with chronic HCV infection with decompensated liver cirrhosis, and group C consists of 30 individuals as control. All patients and control were subjected to full history taking, full clinical examination, complete blood count, liver function tests, renal profile, pelvis-abdominal ultrasound, and serum levels of ACL immunoglobulin G and α-fetoprotein. Results The results showed that seven (23%) of the HCV-positive patients in group A and 18 (60%) of the HCV-positive patients in group B were ACL immunoglobulin G-positive in comparison with none in the control group (0%). Conclusion The prevalence of ACL antibodies is increased during HCV infection, and HCV should be regarded as a possible causative factor in the antiphospholipid syndrome.